2011
DOI: 10.1002/pd.2866
|View full text |Cite
|
Sign up to set email alerts
|

Nonvisualization of fetal gallbladder increases the risk of cystic fibrosis

Abstract: Ultrasonographic evidence of NVFGB is an additional risk factor for CF in cases with FEB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
1
16
1
Order By: Relevance
“…In contrast to previous studies [6,11,22], we did not identify CF in our cohort. This may be explained by the high compliance of our study population to the recommendation to undergo preconception or first-trimester genetic screening tests, including the CFTR gene mutations among the tests recommended by the Israeli Genetic Association.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In contrast to previous studies [6,11,22], we did not identify CF in our cohort. This may be explained by the high compliance of our study population to the recommendation to undergo preconception or first-trimester genetic screening tests, including the CFTR gene mutations among the tests recommended by the Israeli Genetic Association.…”
Section: Discussioncontrasting
confidence: 55%
“…Its absence raises diagnostic questions. It is most important to differentiate between isolated agenesis of the fetal gallbladder, which is considered to be a benign finding [8], and severe diseases such as BA, CF, and other gastrointestinal tract anomalies [10,11,13]. BA is considered to be the leading indication for liver transplantation in childhood [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that various ultrasound digestive abnormalities (USDA), including fetal echogenic bowel (FEB) and fetal intestinal loop dilatation (FILD), may lead to the prenatal diagnosis of CF in 1-7.6% of the cases, especially during the second trimester of pregnancy [4][5][6]. Nonvisualization of the fetal gallbladder (NVFGB) was also reported in affected fetuses, mostly in association with FEB [6][7][8]. Not surprisingly, the triad FEB-FILD-NVFGB had the highest predictive value for CF (likelihood ratio 31.40) [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, it was rarely found as an isolated sign in CF fetuses. In distinct ultrasound (US) series including 226 cases of isolated NVFGB, only 6 CF cases were reported [7][8][9][14][15][16]. Furthermore, in the largest series of 694 cases of USDA who had comprehensive CFTR gene studies, no fetus among the 30 CF cases was found with isolated NVFGB [6].…”
Section: Introductionmentioning
confidence: 99%